Household demand and choice of borrowing source the case of central java - Nina, Takashino (Asian Journal of Agriculture and Development, 2010)
This paper aims to empirically examine determinants of households' borrowing demand and how borrowers choose their lending source. Data sets on rural villagers'financial transactions in Central Java were analyzed. Rural households in Indonesia borrow money from two lending sources: formal and informal. Formal lending sources are primarily government financial institutions, such as banks and cooperatives. Their requirements include written contracts, filling up documents, and proposed collaterals. Informal lending sources include traditional self-help saving groups (called arisan in Javanese), moneylenders, and villagers who provide loan to friends and relatives. Their transactions are not within the control of governmental regulations and are usually based on oral contracts without collateral requirements. ALthough some past studies have described borrowing behavior observed in rural Indonesia (Hamada 2006, Mizuno 1999), empirical studies on borrowing demand and source choice of rural household have been limited. The main contribution of this paper is to fill this gap and to show under what conditions villagers opt to borrow from the informal sector. To invetigate households' borrowing behavior, this paper employs a data set compiled from a survey of 120 households in four hamlets in the rural areas of Yogyakarta province conducted from 2001 to 2005 by researchers of JSPS-DGHE Core University Program. Tobit estimation method was applied to estimate households' loan demand. Multinominal logit estimation method was employed to estimate the probabilities of households borrowing from three possible lending sources: 1) villagers in the research area have access to the formal financial institutions; 2) the observed loan amount is determined by investment opportunities and composition needs, such as housing expenditure, and the level of asset holdings; 3) borrowers choose the lender depending on both material interest rate and psychological cost of trust relationship; and 4) the poor tend to borrow money from arisan more frequently than formal institutions or friends and relatives.